Muscle eye brain disease – A rare case of congenital muscular dystrophy - Vellusamy Subramaniam; Sakthimeena Ramanathan (Indian Journal of Child Health, 2021)
Congenital muscular dystrophies are a distinct group of inherited muscle disorders that manifest within the 1st year of life accompanied by weakness, hypotonia, and developmental delay. A distinguishing feature of congenital muscular dystrophy from other muscular dystrophies is an increased association with brain malformations, particularly disorders of cortical development such as lissencephaly, pachygyria, and polymicrogyria. Moreover, some subtypes of congenital muscular dystrophies (CMDs) such as muscle eye brain disease and Walker-Warburg syndrome are more commonly associated with structural eye abnormalities apart from brain malformations. The inheritance of CMD is usually autosomal recessive except for CMD with spinal rigidity and lamin A/C abnormality and Ullrich CMD.